Nation Branding in Two Major Serbian Music Festivals, Exit and Guca - Gligorijevic Jelena (UNIV CALIFORNIA PRESS, 2022)
This article looks into the nation branding phenomenon surrounding two major Serbian music festivals, Exit and Guc.a, in the post-Milos.evic ' era. The departure point of analysis is the once-dominant national identity narrative of Two Serbias, by which Exit (as a purveyor of Western-style popular music) and Guc.a (as the self-proclaimed guardian of the Serbian brass-band tradition) were pitted against one another as representatives of Two Serbias, one looking towards the West, and the other towards the East. Moving away from this obsolete model of interpretation, this article examines the effects that the inception of nation branding in Serbian public discourse has produced on the local perception of each festival as well as on Serbian national identity within the broader contexts of post-socialist transition, the EU integration, and globalization. It also analyzes the ways in which the principles of market economy and branding practice are being "bastardized" in both festivals, resulting in what Mladen Lazic ' (2003) calls normativevalue dissonance. Nation branding has forged a more unified view of Exit and Guc.a as national brands that ostensibly improve the international image of the country but which in reality deplete both festivals of their initial cultural and political potency. Ultimately, however, the proof of normative-value dissonance in Exit and Guc.a supports the argument that nation branding in these two festivals feeds back into earlier Balkanist discourse on Serbia's indeterminate position between West and East; and it does so in a way that provides little hope for alternative visions of the nation's future.